Optimal asset allocation with factor models for large portfolios - Mohammad Hashem Pesaran; Paolo Zaffaroni (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper characterizes the asymptotic behaviour, as the number of assets gets arbitrarily large, of the portfolio weights for the class of tangency portfolios belonging to the Markowitz paradigm. It is assumed that the joint distribution of asset returns is characterized by a general factor model, with possibly heteroskedastic components. Under these conditions, we establish that a set of appealing properties, so far unnoticed, characterize traditional Markowitz portfolio trading strategies. First, we show that the tangency portfolios fully diversify the risk associated with the factor component of asset return innovations. Second, with respect to determination of the portfolio weights, the conditional distribution of the factors is of second-order importance as compared to the distribution of the factor loadings and that of the idiosyncratic components. Third, although of crucial importance in forecasting asset returns, current and lagged factors do not enter the limit portfolio returns. Our theoretical results also shed light on a number of issues discussed in the literature regarding the limiting properties of portfolio weights such as the diversifiability property and the number of dominant factors.
Keywords: C32; C52; C53; G11; 330; Asset allocation; large portfolios; factor models; diversification; Portfolio-Management; Vermögen; Faktorenanalyse; Prognoseverfahren; Theorie